Problems of revival and development of animal husbandry in Ukraine: Проблемы возрождения и развития отрасли животноводства в Украине - Lavruk, Alexandr; Lavruk, Vitalii (Przegląd Wschodnioeuropejski, 2019)
The problem of revival is considered and the current state of development of animal husbandry in Ukraine is investigated. The research is based on the use of state information resources and generalization of scientific developments of domestic and foreign scientists. The changes in the number of farm animals, the volume of livestock production and improving its economic efficiency are analyzed. It is established that the process of revival should be accompanied by the effective use of own financial resources and ensure the sustainable development of all sub-sectors of animal husbandry. To ensure the implementation of effective measures for the revival, stabilization and development of animal husbandry is possible through the effective use of all types of production resources, in particular the genetic potential of animals, the introduction of innovative technologies and economic levers that contribute to the profitability of animal husbandry. The main factors that directly affect the potential of livestock and poultry and increase its productivity are identified. The necessity of creation of the state special fund for revival and support of animal husbandry is specified and the directions of increase of its effective development are offered.